The Effectiveness of Audio-Assisted Reading to Enhance English Reading Comprehension Skills for Bhutanese Students - Lhamo, Jamyang; Sakulwongs, Nipaporn (THAITESOL Journal, 2023)
The research aimed to assess the English reading comprehension skills of fifth-grade Bhutanese students through a comparison before and after implementing the audio-assisted reading strategy. Additionally, it aimed to investigate the extent of their learning satisfaction towards the use of this strategy. The research was carried out in one of the primary schools in Bhutan for a period of one month. The study adopted a quasi-experimental design employing both qualitative and quantitative methods. Lesson plans were used as the interventional tools while reading comprehension tests and semi-structured interviews were used for the collection of quantitative and qualitative data, respectively. The quantitative data were analyzed using a paired sample t-test, and the qualitative data were analyzed using the thematic analysis technique. The analysis of the pretest and posttest scores revealed that the mean score of the posttest was greater than the mean score of the pretest. The data collected from the interviews revealed that the participants were motivated and satisfied with the use of audio-assisted reading strategy. The study recommends incorporating the audio-assisted reading strategy as an effective reading strategy to enhance the reading comprehension skills of the students.